Bone Marrow-Derived Mesenchymal Stem Cells Migrate toward Hormone-Insensitive Prostate Tumor Cells Expressing TGF-β via N-Cadherin - Jinok Noh (MDPI AG, 2021)
The prostate tumor microenvironment plays important roles in the metastasis and hormone-insensitive re-growth of tumor cells. Bone marrow-derived mesenchymal stem cells (BM-MSCs) are recruited into prostate tumors to facilitate tumor microenvironment formation. However, the specific intrinsic molecules mediating BM-MSCs’ migration to prostate tumors are unknown. BM-MSCs’ migration toward a conditioned medium (CM) of hormone-insensitive (PC3 and DU145) or hormone-sensitive (LNCaP) prostate tumor cells was investigated using a three-dimensional cell migration assay and a transwell migration assay. PC3 and DU145 expressed transforming growth factor-β (TGF-β), but LNCaP did not. Regardless of TGF-β expression, BM-MSCs migrated toward the CM of PC3, DU145, or LNCaP. The CM of PC3 or DU145 expressing TGF-β increased the phosphorylation of Smad2/3 in BM-MSCs. Inactivation of TGF-β signaling in BM-MSCs using TGF-β type 1 receptor (TGFBR1) inhibitors, SB505124, or SB431542 did not allow BM-MSCs to migrate toward the CM. The CM of PC3 or DU145 enhanced N-cadherin expression on BM-MSCs, but the LNCaP CM did not. SB505124, SB431542, and TGFBR1 knockdown prevented an increase in N-cadherin expression. N-cadherin knockdown inhibited the collective migration of BM-MSCs toward the PC3 CM. We identified N-cadherin as a mediator of BM-MSCs’ migration toward hormone-insensitive prostate tumor cells expressing TGF-β and introduced a novel strategy for controlling and re-engineering the prostate tumor microenvironment.